Youth participation in 'post‐secular' times: young Muslim and Buddhist practitioners as religious citizens. (10th April 2018) - Harris, Anita; Lam, Kim
Abstract: Recently there has been renewed interest in the role of religion in the public sphere in the context of a 'post‐secular' age characterized by the resurgence of religious identities and communities in increasingly diverse, multi‐faith societies. Young people's active political and civic engagement has also emerged as a core challenge for robust democracies. While an interesting body of current research suggests that religious commitment may cultivate participation amongst youth by acting as an incubator of civic and political engagement, such literature often positions religiosity as outside of, and consequently at odds with participation in a secular public sphere. We suggest that while religiosity may indeed act as an incubator for civic and political engagement, we propose greater attention to an emergence of alternative, entwined conceptualizations of religious citizenship evident in the practices, performances and dispositions of young Muslim and Buddhist religious practitioners in Australia, whereby processes of individuation contribute to greater fluidity within and across the domains of the religious and the civic.